Michel Foucault view on the Influence of the Philosophy of Language during the Transition to modernity - Abusara, Jamil; Shomar, Towfic (Jordan Journal of Social Sciences, 2021)
This paper is trying to highlight Michel Foucault analysis of the influence of language on the turn toward modernity, where he states that language is an essential transporter of human thinking throughout the eras, the first era is that of 16th century enlightenment where language was still under the Greek’s philosophy that portraits words as an extension of nature, helping researchers to find similarities among things, accordingly science was a search of similarity, and not experimental. In the classical Era of the 17th and 18th century, language was seen as a system of representations, relates words as signifier with signified in an abstract way relieved from ontologies of the past, with very specific use of words, until the era of modernity of the 19th century erupted, the era of (history), where the scoop of thinking is no more dependent on the classical (system) that was related to Beacon’s experimentalism and Descartes’ rationalism, with the agreement and disagreement tables of “scientific method” associated with their discourse. In this era the focus shifted toward the “inner relations” among things that would correlate their use within one specific use. We might see such shift as a shift from “the ego system” toward “language spontaneity”.